2017
DOI: 10.1159/000467897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glycyrrhizin in a Mouse Model of Lung Adenocarcinoma

Abstract: Background: Currently, there is a global attempt to identify potential anti-cancer agents with low toxicity. Previous studies have found that glycyrrhizin exerts anti-cancer action with low toxicity through suppressing thromboxane A2 (TxA2) in lung cancer cell lines. However, these effects have not yet been determined in animal models of lung cancer. Methods: Human lung adenocarcinoma xenografts were established in nude mice by the introduction of A549 cells with stable transfection of the TxA2 receptor (TPα).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…The hydromethanolic root extract of G. glabra also exhibited antimutagenic potential by suppressing micronuclei formation and chromosomal aberration in bone marrow cells of albino mice (V. Sharma, Agrawal, & Shrivastava, ). Glycyrrhizin and glycyrrhetinic acids are effective compounds in gastric cancer treatment, whereas glycyrrhizin suppresses thromboxane A2 in lung cancer cell with low toxicity (Deng, Wang, Zeng, Chen, & Huang, ). According to S. Wang et al (), 18β‐glycyrrhetinic acid has antitumour activities in breast and ovarian cancer, gastric tumours, and leukaemia.…”
Section: Pharmacological Propertiessupporting
confidence: 75%
“…The hydromethanolic root extract of G. glabra also exhibited antimutagenic potential by suppressing micronuclei formation and chromosomal aberration in bone marrow cells of albino mice (V. Sharma, Agrawal, & Shrivastava, ). Glycyrrhizin and glycyrrhetinic acids are effective compounds in gastric cancer treatment, whereas glycyrrhizin suppresses thromboxane A2 in lung cancer cell with low toxicity (Deng, Wang, Zeng, Chen, & Huang, ). According to S. Wang et al (), 18β‐glycyrrhetinic acid has antitumour activities in breast and ovarian cancer, gastric tumours, and leukaemia.…”
Section: Pharmacological Propertiessupporting
confidence: 75%
“…They possess complementary and overlapping mechanisms to slow down the carcinogenic process by scavenging free radicals (Lee et al, 2013), suppressing survival and proliferation of malignant cells (Yan et al, 2018), as well as diminishing invasiveness and angiogenesis of tumors (Lu et al, 2018a). They exert wide and complex range of actions on different molecular targets and signal transduction pathways including membrane receptors (Deng et al, 2017), kinases (Dou et al, 2018), downstream tumor-activator or -suppressor proteins (Adams et al, 2010), transcriptional factors (Zhang et al, 2017b), microRNAs (miRNAs) (Cojocneanu et al, 2015), cyclins, and caspases (Yan et al, 2018).…”
Section: Phytochemicals With Anticancer Propertiesmentioning
confidence: 99%
“…Glycyrrhizin (GA) is the major bioactive component found in licorice roots of a small leguminous shrub, Glycyrrhiza glabra L. In athymic BALB/c nude mice xenograft with human lung adenocarcinoma A549 cells stably transfected with TxA2 receptor (TPa), GA (135 mg/kg) reduced thromboxane synthase (TxAS) and proliferating cell nuclear antigen (PCNA) expression via suppressing TxA2 pathway (Deng et al, 2017). More recent findings showed that GA (100 mg/kg) inhibited the growth of non-small cell lung cancer cells (NSCLC) in patientderived xenograft (PDX) mice by suppressing the level of high mobility group box 1 (HMGB1) and inhibition of JAK/STAT signaling pathway .…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…Glycyrrhizin (GL) is a natural triterpenoid saponin derived from the root of licorice (Glycyrrhiza glabra) that has been associated with numerous pharmacologic effects, including anti-bacterial, antiinflammatory, anti-oxidant, anti-viral, anti-tumor, hepatoprotective, and immunomodulatory activities (19)(20)(21)(22). Stimulation of IL-12 and NO production and suppression of IL-10 production from macrophages (23,24), augmentation of NK cell activity (23), up regulation of costimulatory molecules on dendritic cells (19), increasing of T cells proliferation, reduction of IL-4 production from T cells, direction of immune response toward Th1 (19), are the most important known immunomodulatory activities of GL.…”
Section: Introductionmentioning
confidence: 99%